Solidification of Massive Nodular Cast Iron Mill Rolls in Combined Metal–Sand Molds - Khrychikov, V.; Semenov, O.; Aftandiliants, Y.; Gnyloskurenk, S.; Meniailo, H.; Semenova, T. (Archives of Foundry Engineering, 2026)
At crystallization of castings the various defects such as shrinkage cavities, shrinkage depressions and others are often formed. The purpose of the present work is to experimentally investigate the crystallization process of a massive rolling mill of high-strength cast iron, and to adapt the mathematical model. In the result of the experimental study of the 2160 kg mill roll casting solidification process, the mathematical model was adapted from a reference roll to enable its application to rolls of other sizes. Simulation of ≈7500 kg rolls solidification in combined metal–sand molds revealed the position of the isosolidus fronts, formation of a shrinkage depression on the hot top surface after electroslag heating, and the volume of shrinkage cavities in the hot spot. The volume of the depression was used as the first approximation to estimate the volume of the shrinkage cavity in the hot spot of the casting. This method enables the calculation of chill mass and the elimination of hot spots and shrinkage depressions without the need for complex measuring equipment.